2022
DOI: 10.1177/02692155221111929
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of balance and proprioception exercises in female patients with knee osteoarthritis: A randomized controlled study

Abstract: Objective Loss of proprioception and balance disorders are commonly observed in patients with knee osteoarthritis. In this study, we aimed to investigate the effects of balance and proprioception exercises in patients with knee osteoarthritis. Design A single-center randomized trial with three parallel arms. Setting A tertiary health care facility in Turkey. Participants Female patients with knee osteoarthritis aged 40–70 years. Interventions Ten-week exercise program in Biodex training, classical balance trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Participants were selected and enrolled into the study according to the criteria performed by Kellgren & Lawrence class (II), pain around the knee, and limitation of ROM within the past 6 months [15]. Participants who underwent assessment were excluded from the study if they had: demonstrated any other types of arthritis, swelling around the knee, used of oral or intraarticular corticosteroids (currently or within 6 months), taken physiotherapy treatment for knee OA within 6 months prior to inclusion, uncontrolled hyper-tension, serious cardiovascular problems, a patient with body mass index (BMI) greater than 30, a history of nonsteroidal antiinflammatory drugs (NSAIDs) or consumption of symptomoriented slowacting drugs for OA (e.g., hyaluronic acid or diacerein) a month prior to the assessment date, as well as a diseases that might impact balance [16].…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants were selected and enrolled into the study according to the criteria performed by Kellgren & Lawrence class (II), pain around the knee, and limitation of ROM within the past 6 months [15]. Participants who underwent assessment were excluded from the study if they had: demonstrated any other types of arthritis, swelling around the knee, used of oral or intraarticular corticosteroids (currently or within 6 months), taken physiotherapy treatment for knee OA within 6 months prior to inclusion, uncontrolled hyper-tension, serious cardiovascular problems, a patient with body mass index (BMI) greater than 30, a history of nonsteroidal antiinflammatory drugs (NSAIDs) or consumption of symptomoriented slowacting drugs for OA (e.g., hyaluronic acid or diacerein) a month prior to the assessment date, as well as a diseases that might impact balance [16].…”
Section: Participantsmentioning
confidence: 99%
“…Patients in both groups (A and B) received the same strengthening exercise, which consisted of isometric quadriceps exercise that was performed in 10 repetitions of 6 seconds of contractions each and two seconds of rest periods [16]. In addition, participants in group A received knee stability training exercises, while participants in group B received Biodex Balance training exercises.…”
Section: Interventionsmentioning
confidence: 99%
See 3 more Smart Citations